Health Technology Assessment: Emotional Factors in Decision-Making - Pose Varela, Carlos A.; Borrell Carrió, Francesc (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
Usually in medicine was considered that the technical evaluation and the ethical are different, and that the first has nothing to do with the second. However, it is a mistake to say that science and technology, are completely neutral. Both assessments are based on values and epistemological orientation they have in each historical moment is based on values. In this article we analyze this issue, which has ranged from analysis of emotion to the valuation analysis, and from there to the analysis of decision making. These decisions affect research, technical applications, and also to strictly clinical areas. Patients are not only people with any disease, but also value-laden people that the clinician has to consider. Provide patient care as a moral being is one of the objectives of a value-based medicine and, therefore, patient-centered.